Burocracia, democracia e políticas públicas: Arranjos institucionais de políticas de desenvolvimento - Roberto Rocha C. Pires; Alexandre de Avila Gomide (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– Since the last decade, there has been much debate on the central government's activism in the implementation of development policies that resemble those from Brazil's authoritarian past. However, only rarely, scholars and practitioners have discussed the state capacities that are necessary to execute such policies in the democratic environment, instituted by the 1988 Constitution. This article seeks to understand empirically the interactions between development policies implementation and democratic requisites such as transparency, public participation, and political and bureaucratic oversight, focusing on the tensions and synergies resulting from such interactions and their implications for policy. The paper draws from the comparative analysis of eight case studies of current development policies. The analysis centers on the evaluation of the state capacities created or mobilized during the implementation of such policies. The findings indicate that i) the level of execution of policy goals is associated with the level of technical-administrative capacity that implementation arrangements are able to provide; and ii) the existence and operation of participatory mechanisms, oversight bodies, and interactions with Congress contributed to revisions and innovations during the implementation of these policies. Thus, successful development policies implemented under democratic environments demand not only the technical-administrative capacities necessary for management and execution, but also the political capacities that enable the inclusion of social and political actors, and the processing of conflicts and their potentially divergent interests.
Keywords: H11; H82; O22; 330; bureaucracy; democracy; public policies; state capacity; institutional arrangements